Social Dialogue in Public Sector Reflection about Hungarian and Slovenian approach - Zvone Vodovnik; Aniko Noemi Turi (Central European Public Administration Review)
The process of last years expended enlargement of the European Union leads EU governmental bodies towards enacting new European documents. These documents must be considered as legal bases for making the EU the most dynamic and competitive economy in the world being capable of sustainable economic growth with more and better jobs and greater social cohesion. In the area of the EU legislation the social dialogue must be regarded as an important issue. For time being the EU documents regulate some elements of social dialogue in private sector however, the social dialogue in public sector is still outside of the EU regulation. The paper elaborates a comparative view between two Member States such as Hungary and Slovenia by exploring and analyzing EU industrial relations, and the relationship between the industrial relations of these Member States. It is evident that the EU enlargement has further increased this diversity, and the EU industrial relations in many parts distinguish from national industrial relations. This article analyses the process of the legislative activities at the EU legislative bodies, as well as in the national legislations of Hungary and Slovenia. It emphasizes also the concept of EU industrial relations and shows, which are the frames of the social dialogue in public sector of Hungary and Slovenia.